2013
DOI: 10.1007/s12010-012-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Functional Characterization of Antibiofilm Exopolysaccharide Produced by Enterococcus faecium MC13 Isolated from the Gut of Fish

Abstract: The synthesis and functional characterization of an antibiofilm exopolysaccharide (EPS) from a probiotic Enterococcus faecium MC13 were investigated. The temperature of 35 °C, pH of 6.5, and salinity of 1-2% were found to be optimum for EPS production. The sucrose (30 g l⁻¹) and yeast extract (20 g l⁻¹) acted as suitable carbon and nitrogen sources, respectively, which strongly influenced EPS production with yield of 11.33 and 11.91 g l⁻¹. Based on the thin layer chromatography, EPS of E. faecium MC13 was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 31 publications
5
20
1
Order By: Relevance
“…Lactobacillus strains often produce polymeric substances such as exopolysaccharides (EPS) which enhance the colonization of probiotic bacteria in gastrointestinal tract and helps in modifying the rheological properties and texture of products (Kanmani et al 2013). None of the isolates from fermented foods and beverages in the present investigation displayed bile salt hydrolase activity which was similar to the findings reported by Botes et al (2008) and Quezada et al (2013).…”
Section: Discussionsupporting
confidence: 85%
“…Lactobacillus strains often produce polymeric substances such as exopolysaccharides (EPS) which enhance the colonization of probiotic bacteria in gastrointestinal tract and helps in modifying the rheological properties and texture of products (Kanmani et al 2013). None of the isolates from fermented foods and beverages in the present investigation displayed bile salt hydrolase activity which was similar to the findings reported by Botes et al (2008) and Quezada et al (2013).…”
Section: Discussionsupporting
confidence: 85%
“…faecium MC13 , capable of reducing P . aeruginosa biofilm by 15% 48 . Moreover, a reduction of 86% on biofilm formation was achieved by a treatment with B4-EPS1 from Arthrobacter sp .…”
Section: Resultsmentioning
confidence: 99%
“…EPS is a protection barrier against lethal influence of the environment (desiccation, phagocytosis, phage attack, osmotic stress, antibiotics or toxic compounds) and the major component of bacterial biofilm, enhancing the colonization of probiotic bacteria in cell-host interactions in the gastrointestinal tract [38]. This is a beneficial trait for probiotics in their endeavor to colonize the gut.…”
Section: Exopolysaccharide Production (Eps)mentioning
confidence: 99%
“…Five (7.8%) of our isolates were positive for gelE gene. However, in previous studies, it has been found that strains having this gene did not produce gelatinase [24,38], because the fsr operon could be damaged, lost, or suffer deletions due to physiological stresses from laboratory storage.. Hemolysin production increases the severity of enterococcal infections, and the presence of hemolysin/cytolysin genes is considered a risk pathogenicity factor. Regarding the cylA gene, two (3.1%) isolates gave a positive result, but according to phenotypical tests, only γ-hemolysis was observed.…”
Section: Pathogenicitymentioning
confidence: 99%